أثر الرقابة الداخلية على جودة النظام المحاسبي في الوحدات الحكومية: دراسة حالة وزارة المالية - ولاية النيل الأبيض - د. صلاح محمد ابراهيم أحمد; د. الأمين محمود عبد المجيد; محمد مسعود محمد إدريس (White Nile Journal for Studies and Research, 2020)
The study examined the evaluation of the internal control system with regard to expenditures and revenues in government units. The problem of the study can be manifested in the following questions: What is the effect of internal control on the quality of the system of government units? The study aimed to know the adequacy of the internal control system followed by the Ministry of Finance in the White Nile State in protecting and assets data. The study relied on the historical and deductive approach and is used for public perception and formulation of assumptions and the inductive approach and is used to test the validity of the assumptions, the study concluded that interest in the accounting control system Its improvement makes there an obligation to the fundamentals of the accounting system, and enabling the accounting control system emphasizes the accuracy and quality of accounting information and reduces the opportunities for embezzlement and fraud. The study recommended that attention should be paid to designing and implementing a good accounting control system and applying an inventory system for assets in order to help correct deviations and make there a match between documents and assets, and the need to define tasks and responsibilities and distribute them in order to help in the quality of the outputs of the accounting system.